The influence of foundation mass on dynamic response of track-vehicle interaction - Nguyen, Phuoc T.; Pham, Trung D.; Hoang, Hoa P. (Vietnam Journal of Mechanics, 2019)
The influence of foundation mass on the dynamic response of track-vehicle interaction is studied in this paper. The moving vehicle is modeled as a two-axle mass-spring-damper four-degrees-of-freedom system. A new dynamic foundation model, called "Dynamic foundation model" including linear elastic spring, shear layer, viscous damping and foundation mass parameter, is used to analyze the dynamic response of the track-vehicle interaction. The railway track on the new dynamic foundation model subjected to a moving vehicle is regarded as an integrated system. By means of the finite element method and dynamic balance principle, the governing equation of motion for railway track-vehicle-foundation interaction is derived and solved by the step-by-step integration method. The accuracy of the algorithm is verified by comparing the numerical results with the other numerical results in the literature. The influence of foundation mass parameter on the dynamic response of railway track-vehicle interaction is investigated. The numerical results show that with the new dynamic foundation model the foundation mass effects more significantly on the dynamic response of track-vehicle interaction. The study shows that the new dynamic foundation model describes the true behavior of soil in the analysis of dynamic response of structures on the foundation.